iPhone for Seniors for Dummies - Muir, Nancy C. (Hoboken, New Jersey John Wiley & Sons, Inc., 2016)
Learning to use new technology can be a bit of a challenge for seniors, especially now that smartphones are more like mobile computers. iPhone For Seniors For Dummies, 5th Edition is a full-color text that guides you through easy-to-understand lessons in iPhone features and functions.
Includes Index and Illustrations.
Keywords: iPhone (Smartphone)